New and little known species of Quedius from West Palaearctic (Coleoptera: Staphylinidae: Staphylininae) - Solodovnikov, A. Yu. (Zootaxa, 2005)
Three new species from the Caucasus are described: Quedius (Raphirus) nonseriatus sp. nov., Q. (R.) henrii sp. nov. and Q. (R.) humosus sp. nov. New data on distribution and bionomics are recorded for a rare species, Q. (Microsaurus) bernhaueri Rambousek (southern Macedonia and northern Greece), as well as for little-known Q. (M.) walteri Korge (north-eastern Turkey), Q. (R.) boluensis Korge (northern Turkey) and Q. (R.) semirufus (northern Iran and Azerbaijan). For Q. bernhaueri the type material is examined and the lectotype is designated.